Preparation and application of functionalized nano drug carriers - Rudong Gong; Gaimin Chen (Elsevier, 2016)
Objective: Targeting at category memory characteristics and preparation methods of functionalized nano drugs, preparation technology of functionalized nano drug carriers is studied, and then important role of functionalized nano drug carrier in preparation of medicine is studied. Methods: Carry out the relevant literature search with computer, change limited language in the paper to Chinese and necessarily remove repetitive studies. Results: After first review of 1260 retrieved literature, it can be found that nano drug is with accurate quantity, relatively good targeting, specificity and absorbency. Necessary research of nano drug carriers can prevent and treat disease to a certain extent. Conclusion: Preparation of functionalized nanocarrier is simple and convenient, which can improve frequency of use of nano preparation technology and provide better development space for medical use. Therefore, nanocarriers should be combined with drugs with relatively strong specificity in clinics, in order to be able to conduct effective research on nanometer intelligent drug, effectively promote long-term development of nano biotechnology, and then provide favorable, reliable basis for clinical diagnosis and treatment.